Epidermolysis Bullosa in Chinese Patients: Genetic Analysis and Mutation Landscape in 57 Pedigrees and Sporadic Cases - Yueqian Yu; Zhenzhen Wang; Zihao Mi; Lele Sun; Xi'an Fu; Gongqi Yu; Zheng Pang; Hong Liu; Furen Zhang (Acta Dermato-Venereologica, 2021)

(untitled)
Epidermolysis bullosa encompasses a group of inherited blistering skin disorders. The pathogenic mutations in 10–25% of patients with epidermolysis bullosa have not been identified by Sanger sequencing. The aims of this study were to identify the pathogenic sequence alterations in a large cohort of Chinese patients with epidermolysis bullosa and to clarify the relationship between clinical phenotypes and genotypes. Whole-exome sequencing was performed on 44 pedigrees and 13 sporadic cases. The results were further confirmed by Sanger sequencing. In total, 52 mutations, comprising 19 novel and 33 previously reported mutations, were identified in 5 genes, with a mutation detection rate of 100%. A relationship between subtypes and pathogenic genes was established: 12 cases of epidermolysis bullosa simplex were associated with mutations in KRT5/14 and PLEC; one case of junctional epidermolysis bullosa carried mutations in ITGB4; and 44 cases of dystrophic epidermolysis bullosa were caused by mutations in COL7A1. The results of this study support whole-exome sequencing as a promising tool in the genetic diagnosis of epidermolysis bullosa.